Identification of the poorest and the impact of credit on them: the case of BRAC - Halder, Shantana R.; Husain, A.M.M. (BRAC, 2019)
This study offers a new approach for identification of the poorest and constructs a poverty profile by integrating four non-impact variables sensitive to poverty. Poverty was found to be highly correlated with all of the variables included in the index namely sex, occupation and education Ievel of the household head, village Ievel economic development and household landholding. Results on the impact of micro-credit programme on the poorest show that the poorest with little asset base received similar amount of credit as other members but invested it in relatively more non-productive activities. The poorest BRAC members consumed more calorie and owned more non-land assets than the poorest of the comparison group. For BRAC members length of membership influencer negatively in their calorie consumption level and asset accumulation.